Dwarfism and insulin resistance in male offspring caused by α1-adrenergic antagonism during pregnancy - Rebecca Oelkrug; Beate Herrmann; Cathleen Geissler; Lisbeth Harder; Christiane Koch; Hendrik Lehnert; Henrik Oster; Henriette Kirchner; Jens Mittag (Elsevier, 2017)
Objective: Maternal and environmental factors control the epigenetic fetal programming of the embryo, thereby defining the susceptibility for metabolic or endocrine disorders in the offspring. Pharmacological interventions required as a consequence of gestational problems, e.g. hypertension, can potentially interfere with correct fetal programming. As epigenetic alterations are usually only revealed later in life and not detected in studies focusing on early perinatal outcomes, little is known about the long-term epigenetic effects of gestational drug treatments. We sought to test the consequences of maternal α1-adrenergic antagonism during pregnancy, which can occur e.g. during hypertension treatment, for the endocrine and metabolic phenotype of the offspring. Methods: We treated C57BL/6NCrl female mice with the α1-adrenergic antagonist prazosin during pregnancy and analyzed the male and female offspring for endocrine and metabolic abnormalities. Results: Our data revealed that maternal α1-adrenergic blockade caused dwarfism, elevated body temperature, and insulin resistance in male offspring, accompanied by reduced IGF-1 serum concentrations as the result of reduced hepatic growth hormone receptor (Ghr) expression. We subsequently identified increased CpG DNA methylation at the transcriptional start site of the alternative Ghr promotor caused by the maternal treatment, which showed a strong inverse correlation to hepatic Ghr expression. Conclusions: Our results demonstrate that maternal α1-adrenergic blockade can constitute an epigenetic cause for dwarfism and insulin resistance. The findings are of immediate clinical relevance as combined α/β-adrenergic blockers are first-line treatment of maternal hypertension.